Low-Cost Bioethanol Distiller with PV Modules as Educational Media in Renewable Energy Vocational Schools - Nursyahied, Imam; Priyanto, Sugeng; Syahrir, Syahrir (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The transition to renewable energy is crucial for meeting rising global energy demand while mitigating climate change. Bioethanol, a renewable fuel produced from biomass, is widely used to reduce emissions in the transport sector. This study develops a low-cost bioethanol distiller integrated with photovoltaic (PV) modules as a hands-on educational tool for vocational students. The distiller was constructed from affordable, locally available materials and powered by a small off-grid PV system. Experimental trials were conducted using fermented feedstock to produce ethanol, measuring output volume, purity, energy consumption, and system efficiency. The results show that the solar-powered distiller can produce high-purity ethanol (approximately 75–90% v/v) at a rate of about 0.4–0.5 L per batch (5 L feed of 10% ethanol) in 2 hours. The electrical energy consumption per batch 600 Wh was supplied entirely by a 150 WP solar panel and battery storage. The ethanol produced is suitable as a fuel blend, and the system demonstrated an energy-efficient operation for its scale. Students engaging with the distiller reported improved understanding of biofuel production and solar energy integration. In conclusion, the proposed system provides a cost-effective and sustainable learning media for renewable energy education, illustrating key concepts of biofuel production and solar power utilization. This low-cost distiller can be readily adopted in renewable energy vocational schools and scaled for broader educational outreach and community-level bioethanol production.